Viscoelastic behaviour of heat-treated whey protein concentrate suspensions - Meza, Barbara Erica del Valle (2009)
The viscoelastic behaviour of heat-treated whey protein concentrate (WPC) suspensions was studied. Suspensions with total protein (TP) content of 5% and 9% w/v prepared from a commercial WPC with 38% w/w protein were treated at two temperatures (72.5 and 77.5 ºC) during selected times to obtain 60% of denatured protein content. Unheated WPC suspensions were used as control. Frequency sweeps were performed in the range of 0.01–10 Hz at 20 ºC. Mechanical spectra of WPC suspensions were similar to viscoelastic fluids. However, unheated WPC suspensions showed some mechanical characteristics of colloidal crystals, like little dependency of elastic (G0) and viscous (G00) moduli with TP content, solid-like mechanical spectra, and difficulty to flow at low content of TP. At a selected frequency of 1 Hz, viscous modulus was more frequency (u) dependant on experimental conditions (TP and temperature) than elastic modulus. Mechanical spectra were modelled using power law equations (G0 ¼ aux, G00 ¼ buy), but only parameters of heat-treated WPC suspensions containing 9% of TP showed temperature dependency. Characteristic relaxation times (sc) were calculated as the inverse of the crossover frequency, where G00 ¼ G0. Heat treatments produced a decrease in the extent of the elastic behaviour because heat-treated WPC suspensions presented higher phase angle and smaller sc values than unheated WPC suspensions for the same TP content. The sc decreased when treatment temperature increased but only in heattreated WPC suspensions with 5% of TP.